Transparency Measures in the Trade Facilitation Agreement: Have these improved the scope of GATT Article X? - Shumba, Willie (Acta Universitatis Danubius. Juridica, 2025)
Article X of GATT 1994 represents the first attempt to make trade laws fair, transparent and predictable in order to facilitate trade at a global level. The background of these provisions can be traced as far back as GATT 1947. With effect from February 2017, a new Trade Facilitation Agreement (TFA) of the World Trade Organisation (WTO) entered into force. The TFA reviewed Article X, and it identified additional measures which are designed to facilitate international trade. This study examines how the TFA has improved and clarified the provisions stipulated in Article X. This was a desk study whose main sources of data were the legal instruments of the WTO and a review of published literature. It was a comparative analysis of Article X and the corresponding provisions laid down in the TFA. The study found that TFA has made significant improvements to Article X, all designed to make the international trade environment more transparent and predictable and thus expedite the movement of goods across borders. The TFA also makes the WTO Members more accountable to one another in the way they process international trade. The study therefore adds knowledge to academia and practitioners engaged in international trade.